Effect of Oxygen Impurity on Nitrogen Radicals in Post-Discharge Flows. (10th December 2015) - Shiba, Yoshinobu; Teramoto, Akinobu; Suwa, Tomoyuki; Watanabe, Kensuke; Nishimura, Shinichi; Shirai, Yasuyuki; Sugawa, Shigetoshi
Abstract : Because oxygen impurity in the silicon nitride film deteriorate the quality of the nitride film it is important to research the behavior of oxidizing species during the nitride formation process. We investigate the effect of oxygen molecules in the ground state on nitrogen radicals in post-discharge flows using ultra clean gas supply technology. Although oxygen atoms are not only excited directly by the discharge process, but the N2 O and O3 are also generated in the gas. The nitrogen radicals in mixture gas of O2 and nitrogen radical easily excite the oxygen molecules and they become oxidizing species. As a result, the nitrogen radicals are inactive, and then oxygen impurity must be reduced in the process using nitrogen radicals.